Socio-Economic Determinants Of Crime In Central Java: Spatial Econometrics Analysis - Fadhillah, Muhammad Farhan; Setyorini Gunawan, Diah; Bambang, Bambang (Jurnal Ekonomi Kuantitatif Terapan; Vol 18 No 1 (2025): Vol. 18, No. 1, FEBRUARI 2025 (pp.1-149)DO - 10.24843/JEKT.2025.v18.i01.P05, 2025)
Several previous studies have proven that low socio-economic factors are the causes of crime. Central Java is a province with a fairly low level of socio-economic welfare. However, this province is also one of the provinces with the lowest crime rate in Indonesia. This research aims to prove the socio-economic factors including poverty, education, unemployment, income per capita, and area effect on the total crime in all districts of Central Java. This research is a quantitative research using the panel data from 35 districts of Central Java in the period of 2018-2022. The data was analyzed using spatial econometric methods with a panel data approach. Based on the results of Spatial Auto Regressive (SAR) with Fixed Effect Model (FEM) shows that education and income per capita have significant negative impact on crime. Keywords: Econometrics, Crime, Spatial Classification JEL: C49, K42, R12